New plastic formations in the Anthropocene - De-la-Torre, Gabriel Enrique; Dioses-Salinas, Diana Carolina; Pizarro-Ortega, Carlos Ivan; Santillán, Luis (The Science of the total environment, 2021)
Plastic pollution is one of the major challenges in the Anthropocene. Upon reaching the marine environment, plastic debris is subject to anthropogenic and environmental conditions that result in novel items that vary in composition, physical and chemical characteristics. Here, we reviewed and discussed the potential fate and threat to the environment of four recently described plastic formations: Plastiglomerates, pyroplastics, plasticrusts, and anthropoquinas. The threats identified were mostly related to the release of toxic chemicals and plastic ingestion. Transportation of alien invasive species or microbial pathogens and fragmentation of larger plastics into microplastics (<5 mm), potentially reaching marine trophic webs, are suspected as potential impacts based on the characteristics of these plastic formations. Some plastic forms may persist in the environment and voyage across the ocean, while others are denser and less likely to enter the plastic cycle or interact with biota. In the latter case, plastics are expected to become buried in the sediment and incorporate into the geological record. It is necessary to establish sampling protocols or standards that are specific to each plastic formation and start reporting the occurrence of these new plastic categories as such to avoid underestimating plastic pollution in marine environments. It is suggested that monitoring plans include these categories and identify potential sources. Further research must focus on investigating whether the suspected impacts are a matter of concern. In this sense, we have suggested research questions to address the knowledge gaps and have a better understanding of the impacts and distribution of the new plastic forms. [Display omitted] •New plastic-associated contaminants have been recently reported in literature.•The fate and effects depend on the characteristics of each new contaminant.•Plastic pollution monitoring guidelines must include the new terminology.•Further research is needed regarding the suspected impacts of these contaminants.